‍Identifying Critical Success Factors of Knowledge Management System in Academic Centers & Faculties of Tehran - Farajollah Rahnavard; Asghar Mohammadi (Journal of Information Technology Management)
In the third millennium, we observe rapid changes in technologies and intense complexity in environment. In such an environment, developing competitive advantage necessitates new kind of organizations which are capable of knowledge creation. Hence, it is expected that managers to have a deep perception of prerequisites of knowledge management and enhance the organizational performance through investment in knowledge-based projects. The most important pace in this regard is to recognize the effective factors in implementation of knowledge management. This research has focused on critical success factors (CSFs) of knowledge management system in public administration faculties and higher education institutes in Iran. Findings is indicative of following key factors: 1) Human resource development; 2) knowledge-oriented strategic direction; 3) information system infrastructures; 4) participative culture; 5) benchmarking; 6) knowledge evaluation and transformation; and 7) people involvement.